Mucosal Serpin A1 and A3 Levels in HIV Highly Exposed Sero‐Negative Women are Affected by the Menstrual Cycle and Hormonal Contraceptives but are Independent of Epidemiological Confounders. (13th September 2012) - Rahman, Syeda; Rabbani, Rasheda; Wachihi, Charles; Kimani, Joshua; Plummer, Francis A.; Ball, Terry B.; Burgener, Adam
Abstract : Objective: Serpins (serine protease inhibitors) are associated with protection against HIV infection. Here, we characterized mucosal serpin expression in the genital tract of HIV highly exposed sero‐negative (HESN) women meeting our epidemiological definition of HIV resistance in relation to epidemiological variables. Methods: Cervicovaginal lavage (CVL) fluid and plasma were collected from 84 HIV‐resistant, 54 HIV‐uninfected, and 66 HIV‐infected female commercial sex workers. Serpin A1 and A3 concentrations were measured by ELISA and compared with clinical information. Results: Mucosal serpin A1 was elevated during proliferative phase over secretory phase ( P  = 0.017*), while A3 remained similar ( P  = 0.25). Plasma and mucosal serpin A1/A3 levels were not associated with each other and appeared compartment specific ( r  = 0.21, r  = 0.056). Serpin A1/A3 expression did not associate with age ( r  = 0.009, r  = −0.06), duration of sex work ( r  = 0.13, r  = −0.10), clients per day ( r  = −0.11, r  = −0.02), concurrent STIs ( P  = 0.36, P  = 0.15), but was lower in women using hormonal contraceptives ( P  = 0.034, P  = 0.008). Mucosal serpin A1/A3 levels in HIV‐infected individuals were not significantly different with disease status as determined by plasma CD4 + T‐cell counts ( P  = 0.94, P  = 0.30). Conclusion: This study shows the relationship of serpins to the menstrual cycle and hormonal contraceptives, as well as their independence to epidemiological sexual confounders. This information provides a broader understanding of innate components of the mucosal immune system in women.